Theoretical analysis of possibility of electromagnetic wave phase front curvature physical phenomenon application in stationary microwave radio systems (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
The results of mathematical modelling of electromagnetic wave amplitude and phase distributions on receive array aperture are shown. From its analysis evidently that electromagnetic wave phase front curvature theoretically can be applied for two source of radiation discrimination in stationary microwave radiolinks. This gives possibility for reusing radiowave spectrum.